Ethical Issues in Outsourcing: The Case of Contract Medical Research and the Global Pharmaceutical Industry - Adobor, Henry (2012)
The outsourcing of medical research has become a strategic imperative in the global pharmaceutical industry. Spurred by the challenges of competition, the need for speed in drug development, and increasing domestic costs, pharmaceutical companies across the globe continue to outsource critical parts of their value chain activities, namely contract clinical research and drug testing, to sponsors across the globe, typically into emerging markets. While it is clear that important ethical issues arise with this practice, unraveling moral responsibility and the allocation of responsibility is not so clear, considering that contracts, by their very definition transfer responsibility from the principal to the agent. This research provides a framework for exploring some of the ethical issues, including attributions of moral responsibility associated with Contract Medical Research. Using a theory of strategic and moral behavior, the research shows that both clients and sponsors in contract research have individual and collective responsibility to ensure that due care and diligence is exercised in the performance of clinical research. The research suggests some guidelines for stakeholder action.
Keywords: Corporate Social Responsibility; Contract research; Moral Responsibility; Moral Theory; Ethics; Outsourcing